On the Relationship of Ostracod Species (Crustacea) to Shallow Water Ion and Sediment Phosphate Concentration Across Different Elevational Range (Sinop, Turkey) - (:unkn) unknown (CENTRAL FISHERIES RESEARCH INST, 2017)
In order to investigate the relationship of freshwater ostracods with some of those physico-chemicals and sediment phosphate concentrations, 97 shallow aquatic bodies were sampled during July 2014 in the Sinop province (Turkey). A total of 3083 individuals belonging to 28 ostracod taxa are reported from 76 of 97 sites. While 24 of these taxa were firstly reported from the province, Bradleytriebella tuberculata is a newly reported species for Turkish Ostracoda fauna. Species diversity (H'=1.87) increased around the middle elevations (601-750 m) whereas it was decreased in low and high elevations. Results of ANOSIM analyses exhibited no significant difference among species composition of eight groups with 150 m elevational range (P>0.05). Cosmoecious species occurred in almost all elevational ranges whereas others seemed to prefer low to middle elevational ranges. A significant effect of water temperature, magnesium content of water, and total organic phosphate of sediments (P<0.05) were observed on ostracod assemblages. It appears that rather than number of sampling sites, habitat quality and spatial differences played critical roles on the species diversity.
Keywords: Ostracoda; cosmoecious species; diversity; phosphate; bioindicator; ECOLOGICAL CHARACTERISTICS; ALTITUDINAL RANGES; REGION TURKEY; TRACE-METALS; DIVERSITY; HABITAT; LAKE; RECONSTRUCTION; PROVINCE; REQUIREMENTS